First Successful Application of Preimplantation Genetic Diagnosis for Lethal Neonatal Rigidity and Multifocal Seizure Syndrome in Korea: A Case Report - Gyeong Eun Yeom; Young Hwa Jung; Soo Yeon Kim; Sun Ah Choi; Hunmin Kim; Chang Won Choi (Korean Society of Neonatology, 2022)
Lethal neonatal rigidity and multifocal seizure syndrome (RMFSL) is a severe autosomal recessive epileptic encephalopathy characterized by rigidity, intractable multifocal seizures, microcephaly, apnea, and bradycardia immediately after birth. RMFSL is related to a mutation in breast cancer 1-associated ataxia telangiectasia mutated activation-1 protein (BRAT1). We report a case of a female infant born to non-consanguineous Korean parents who developed hypertonia, dysmorphic features, progressive encephalopathy with refractory seizures at birth, and worsening intermittent apnea, leading to intubation and death at 137 days of age. The initial repeated electroencephalographic findings were normal; however, a pattern of focal seizures emerged at 35 days of life. Rapid trio whole-exome sequencing revealed heterozygous mutations c.1313_1314delAG p.(Gln438Argfs*51) and c.1276C>T p. (Gln426*) in BRAT1. After genetic counseling for pregnancy planning, a preimplantation genetic diagnosis for targeted BRAT1 mutations was successfully performed, and a healthy baby was born. To our knowledge, this is the first reported case of a Korean patient with compound heterozygous mutations in BRAT1. An early and accurate genetic diagnosis can help provide timely treatment to patients and indicate the need for reproductive counseling for parents for family planning.